Whole-genome DNA methylation profiling reveals epigenetic signatures in developing muscle in Tan and Hu sheep and their offspring - Yue, Caijuan; Wang, Jiakang; Shen, Yifei; Zhang, Junli; Liu, Jian; Xiao, Aiping; Liu, Yisha; Eer, Hehua; Zhang, Qiao-e (Frontiers in Veterinary Science, 2023)
The Tan sheep is a popular local breed in China because of tenderness and flavor of its mutton. The Hu sheep breed is also famous for its high litter size, and its muscle growth rate is faster than that of Tan sheep. However, the epigenetic mechanism behind these muscle-related phenotypes is unknown. In this study, the longissimus dorsi tissue from eighteen 6-month-old Tan sheep, Hu sheep and Tan-Hu F2 generation (six sheep per population; feed was consistent after weaning) were collected. After genomic DNA extraction, whole-genome bisulfite sequencing (WGBS) and bioinformatics analysis were performed to construct genome-wide DNA methylome maps for the Tan sheep, Hu sheep and their Tan-Hu F2 generation. Distinct genome-wide DNA methylation patterns were observed between Tan sheep and Hu sheep. Moreover, DNA methylated regions were remarkably increased in the skeletal muscle from Tan sheep vs. the F2 generation compared to the Hu sheep vs. F2 generation and the Tan sheep vs. Hu sheep. Compared with Hu sheep, the methylation levels of actin alpha 1 (ACTA1), myosin heavy chain 11 (MYH11), Wiskott-Aldrich syndrome protein (WAS), vav guanine nucleotide exchange factor 1 (VAV1), fibronectin 1 (FN1) and Rho-associated protein kinase 2 (ROCK2) genes were markedly distinct in the Tan sheep (P-value ≤ 0.05 and |log2 (fold-change)| ≥ 2). Furthermore, GO analysis indicated that these genes were involved in the terms of myotube differentiation, myotube cell development, smooth muscle cell differentiation and striated muscle cell differentiation. Taken together, the findings from this study, in addition to data from previous research, demonstrated that the ACTA1, MYH11, WAS, VAV1, FN1 and ROCK2 genes may exert regulatory effects on muscle development.